Dental microwear texture analysis in mammalian ecology. (20th January 2016) - Calandra, Ivan; Merceron, Gildas
Abstract: Neoecology and paleoecology both seek to answer the same questions, albeit using different material, at different time scales and with different limitations. Nevertheless, too often, neoecologists neglect paleoecology, and paleoecologists only use neoecology as a baseline for actualism. One reason for this is the lack of tools that can be applied to both fields. This is a review of the contributions to both neoecology and paleoecology of three‐dimensional (3D) dental microwear texture analysis (DMTA), a method that can act as a bridge between these fields. DMTA studies can be grouped according to the type of ecological questions researchers seek to answer: specific ecology, intra‐specific ecology, niche partitioning and dietary overlap, and ecology over time. The first question has been the main focus of research; the other three were only superficially studied. In this review, selected examples will be presented to demonstrate that DMTA, as one of the few tools that can be applied to both modern and fossil samples, has been used to address key ecological questions in mammalian neoecology and paleoecology. With the wide range of neoecological and paleoecological questions that DMTA can answer, it is clear that this methodology will be used increasingly in the future, possibly in combination with other ecological proxies.